2020
DOI: 10.1515/eng-2021-0009
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of EMG Signals during Stance and Swing Phases for Controlling Magnetorheological Brake applications

Abstract: The development of ankle foot orthoses (AFO) for lower limb rehabilitation have received significant attention over the past decades. Recently, passive AFO equipped with magnetorheological brake had been developed based on ankle angle and electromyography (EMG) signals. Nonetheless, the EMG signals were categorized in stance and swing phases through visual observation as the signals are stochastic. Therefore, this study aims to classify the pattern of EMG signals during stance and swing phases. Seven-time doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…Parameter yang dimaksud adalah jumlah lapisan tersembunyi, jumlah neuron, dan fungsi aktivasi. Untuk proses pembelajaran/training, algoritma yang digunakan adalah Levenberg-Marquardtz yang telah terbukti kemampuannya dalam proses optimasi pencarian nilai parameter di dalam arsitektur atau struktur JST [17].…”
Section: Variasi Data Dan Hyperparameterunclassified
“…Parameter yang dimaksud adalah jumlah lapisan tersembunyi, jumlah neuron, dan fungsi aktivasi. Untuk proses pembelajaran/training, algoritma yang digunakan adalah Levenberg-Marquardtz yang telah terbukti kemampuannya dalam proses optimasi pencarian nilai parameter di dalam arsitektur atau struktur JST [17].…”
Section: Variasi Data Dan Hyperparameterunclassified
“…EMG features have been calculated in other studies [17], [19], [20]. Some studies used 5 time-domain features [17] and other used 14 time domain features [19], meanwhile, another incorporated 11 EMG features with time domain and frequency domain combination [20]. The gap between this study's analysis and another study lies in the various transfer function combinations used, and the 12 features consist of both time-domain and frequency-domain features.…”
Section: Introductionmentioning
confidence: 98%
“…A study found that complicated data acquisition protocol can increase the ANN accuracy [15], the study used the sigmoid function as one of the layers. EMG features have been calculated in other studies [17], [19], [20]. Some studies used 5 time-domain features [17] and other used 14 time domain features [19], meanwhile, another incorporated 11 EMG features with time domain and frequency domain combination [20].…”
Section: Introductionmentioning
confidence: 99%